Clinical Spectrum and Etiology of Neonatal Cholestasis: Experience in a tertiary care hospital of Bangladesh (Journal of Dhaka National Medical College & Hospital, 2016)
Background: Misdiagnosis of neonatal cholestastatic jaundice as physiological jaundice delays the identification of important liver diseases.Objectives: Aim of this study was to observe the clinical spectrum and etiologies of neonatal cholestasis.Methods: This cross-sectional study was conducted at the department of Pediatric Gastroenterology and Nutrition of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from August 2013 through July 2015 among purposively sampled infants with neonatal cholestasis. For all patients, serum bilirubin total, direct and liver function tests were checked. Investigations were done for diagnosis of cause. Hepatobiliary scintigraphy and liver biopsy was done in all except those where diagnosis was otherwise confirmed.Results: Total 124 neonatal cholestasis cases were studied and most of them 95(76.6%) were male. The mean age at admission was 83.6±40.3 days and mean age at onset of jaundice was 6.75±7.3days. The most common causes of neonatal cholestasis were idiopathic neonatal hepatitis (48, 38.7%), BA (38, 30.6%), congenital cytomegalovirus hepatitis (15,12.1%) and Hypothyroidism (7,5.6%) respectively. Common clinical features at presentation were jaundice (100%), pale colored stools (100%), hepatomegaly (100%) and splenomegaly (38.4%) respectively. Term baby, good birth weight and persistent pale colored stool were significantly higher in BA cases.Conclusion: Among studied subjects Biliary atresia was found to be the most common identifiable cause of neonatal cholestasis. No single clinical feature was found to be significant for differentiating the causes. Jaundice with pale coloured stool and hepatomegaly was found to be the most common presenting clinical features of neonatal cholestasisJ. Dhaka National Med. Coll. Hos. 2016; 22 (02): 09-12